Synthesis and formation mechanism of submicrometer ZrB2 powders via the Pechini-type polymerizable complex route. Issue 96 (17th October 2015) - Yan, Chunlei; Liu, Rongjun; Zhang, Changrui; Cao, Yingbin; Long, Xianhai
<x xml:space="preserve">Abstract</x> Synthesis and formation mechanism of submicrometer ZrB2 powders via the Pechini-type route.